18 The evidence-based clerking proforma. (3rd November 2019) - Ellis, L; Omar, I; Padmagirison, R
Abstract : The clerking document is the essential starting point of each admission. Blank continuation sheets are not easily identifiable in the notes, can get lost, and do not contain any speciality-relevant 'prompts'. This affects the quality of the clerking, and therefore the quality of care. We formulated a list of 'essential' clerking items. RCOG states that a working diagnosis should be presented within 24 hours of admission, a plan should be documented for all unscheduled admissions, and each woman should be seen by a consultant gynaecologist within 14 hours of admission; these were included. We formalised this into 21 'clerking criteria'. 25 emergency gynaecology admissions were randomly selected from one month. Notes were retrospectively analysed, clerking documents were assessed for each criterion. The Results showed room for improvement; consultant responsible was 0% recorded. The mean recording of the 21 criteria was 50.8%. We then created a proforma, which was subsequently peer-reviewed, and implemented. 25 proformas were randomly selected and retrospectively analysed from one month. We held our proforma to the original set of 21 criteria. Documentation significantly improved with use of the proforma. Documentation of 20 of 21 criteria improved. The responsible consultant documentation improved from 0% to 68%. Documentation of a working diagnosis rose from 40% to 92%. The mean overall documentation was 78%. We became leaders because we noticed an aspect of our daily work that could be improved, and we took initiative to create a solution, and to objectively assess the improvement. Despite being FY2 doctors, we were able to make a positive change affecting both the team and the patient. The rotation of juniors is often viewed as a negative for the departments; new doctors require more supervision. However, we believe it allows transfer of ideas between departments, for the betterment of each.